The Use of Task-Based Language Instruction in Teaching Multigrade Elementary Students on English Private Course - Rizqi Febrian Pramudita (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: There are some ways to broaden learner’s ability in acquiring English nowadays. In formal school, the students commonly learn English with their classmate in the same level of grade. Nevertheless, by any circumstance, studying English in formal school should be committed within various grades of students, which can be called as multigrade class. It should be underlined that those studies are applied in formal school of rural area. However, in fact, multigrade class may happen in informal educational institution such as English course. This study is conducted to know whether or not there is a significant effect of teaching multigrade primary level students in regular class of an English private course to the progres of the students’ speaking performance by using Task-based Language Instruction. Therefore, the focus of the students’ competence is the fluency of their speaking and behavior during teaching learning activities. Keywords: Task-based language instruction, multigrade elementary students, English private course.